Pengaruh Metode Pembelajaran Kooperatif Tipe Make-a-Match terhadap Minat Belajar Matematika Siswa SMA Negeri 4 Yogyakarta (Indo-MathEdu Intellectuals Journal, 2026)
This study investigates the impact of the "Make-a-Match" method on students' interest in mathematics at SMA Negeri 4 Yogyakarta, while assessing whether its effectiveness differs significantly from conventional teaching approaches. The research employed a quantitative methodology with a quasi-experimental, non-equivalent control group design. Data were gathered through a learning interest questionnaire, which was rigorously validated by subject matter experts and confirmed reliable through analysis using Excel and IBM SPSS 25 for Windows. Statistical analysis was performed using paired and independent sample t-tests at a 5% significance level, ensuring all data met the required assumptions for normality and homogeneity. In instances where these assumptions were not met, Wilcoxon and Mann-Whitney tests were utilized as non-parametric alternatives. The findings reveal that the "Make-a-Match" method has a positive and significant influence on students' interest in learning mathematics at SMA Negeri 4 Yogyakarta. While the comparative analysis did not show a statistically significant difference between the "Make-a-Match" and conventional groups, a critical distinction emerged: the "Make-a-Match" method produced a significant improvement in student interest, whereas the conventional method showed no such effect. This indicates that the "Make-a-Match" approach is a more effective strategy for fostering mathematical interest among students compared to traditional teaching methods.